Man’s change in the face of Nothingness: from anguish to liberation - Godínez, Héctor Sevilla (Advances in Social Sciences Research Journal, 2019)
The article contains a set of reflections regarding the change that corresponds to man when he is able to recognize himself before the abysm of nothingness. Obviously, this encounter with nothingness generates anguish, which can be an obstacle for liberation. In such a manner, the intention of this text is to present anguish as a consequence of uncertainty, which is propitiated by the human need to have everything under control; in that sense, overcoming the anguish before nothingness will allow man to recognize it as a guideline and possibility of liberating himself from the structures that suffocate and condition the individual. Under that optic, the article ends referring to the ineludible characteristic of change and the importance of recognizing, as human beings of the contemporary world, the nothingness implicit in the being.